(untitled) (Journal of Educational Sciences, 2022)
Today, ethnic revival is considered to be one of the leading directions in the development of mankind. Beginning of the 21st century characterized by the fact that humanity is moving from a technogenic culture to a humanitarian one, the highest values of which are man, nature, family, peace. Traditional folk culture has a positive historical experience that requires its study and implemantation in new conditions. At the same time, education has the task of preserving the native culture of peoples. The success of the transformation of society will largely depend on how much the need for the revival of the spirituality and national identity of each people will be satisfied. People want to know their native culture, their language, to feel their belonging to a certain ethnic group. The leading place in solving these problems is given to the education system built on ethno-cultural foundations, on the principle of dialectical trinity: national, international and global, which allows a person to deeply feel belonging to his people and at the same time recognize himself as a citizen of the country and a subject of world civilization. Traditional folk culture should be connected with the educational process with the educational institution. The article deals with the concept of communicative-ethnopedagogical competence and its significance in education. There are three styles of communicative-ethnopedagogical competence. Keywords: communicative-ethnopedagogical competence, ethnopedagogics, communication, competence, higher education, future teachers.